Does the Qatar Map of the Tigris and Euphrates belong to Evliya Celebi? - (:unkn) unknown (ISAM, 2012)
This article discusses the map of the Tigris and Euphrates in the private collection of Shaikh Hassan bin Muhammad al-Thani of Qatar. Through a detailed comparison of the map with the text of Evliya Celebi's (1611-c.1685) Seyahatname (Book of Travels), this study demonstrates that the map in question was drawn up either by Evliya himself or else by someone in his retinue and under his supervision.
Keywords: the Qatar Map of the Tigris and Euphrates; Seyahatname; Evliya Celebi